A Substituted Diphenyl Amide Based Novel Scaffold Inhibits Staphylococcus aureus Virulence in a Galleria mellonella Infection Model - Mishra, Biswajit; Khader, Rajamohammed; Felix, Lewis Oscar; Frate, Marissa; Mylonakis, Eleftherios; Meschwitz, Susan; Fuchs, Beth Burgwyn (Frontiers in Microbiology, 2021)
Antimicrobial compounds can combat microbes through modulating host immune defense, inhibiting bacteria survival and growth, or through impeding or inhibiting virulence factors. In the present study, a panel of substituted diphenyl amide compounds previously found to disrupt bacterial quorum sensing were investigated and several were found to promote survival in the Galleria mellonella model when provided therapeutically to treat a Gram-positive bacterial infection from methicillin-resistant Staphylococcus aureus strain MW2. Out of 21 tested compounds, N-4-Methoxyphenyl-3-(4-methoxyphenyl)-propanamide (AMI 82B) was the most potent at disrupting S. aureus virulence and promoted 50% larvae survival at 120 and 96 h when delivered at 0.5 and 5 mg/Kg, respectively, compared to untreated controls (p < 0.0001). AMI 82B did not exhibit G. mellonella toxicity (LC50 > 144 h) at a delivery concentration up to 5 mg/Kg. Further assessment with mammalian cells suggest AMI 82B hemolytic effects against erythrocytes has an HL50 greater than the highest tested concentration of 64 g/mL. Against HepG2 hepatic cells, AMI 82B demonstrated an LD50 greater than 64 g/mL. AMI 82B lacked direct bacteria inhibition with a minimal inhibitory concentration that exceeds 64 g/mL and no significant reduction in S. aureus growth curve at the same concentration. Assessment via qPCR revealed that AMI 82B significantly depressed quorum sensing genes agr, spa, and icaA (p < 0.05). Thus, AMI 82B therapeutic effect against S. aureus in the G. mellonella infection model is likely an influence on bacterial quorum sensing driven virulence factors and provides an interesting hit compound for this medically important pathogen.